Curriculum development of a flipped classroom in general chemistry - Kaufman, Lisa (My University, 2014)
This paper explores one possible solution to the best use of class time in a high school chemistry classroom. Many classrooms are taught through a lecture style where the content is taught in class and the student tries to apply the content by doing problems at home. Students most need a teacher's help while working through and applying the content though, not during a lecture of the content. This curriculum change intended to give students more time in class with the teacher to help understand the curriculum while watching a video of the lecture before coming to class. In class the next day, students would apply the content with the teacher there to help. This is called a flipped classroom. This style of teaching and learning showed a slight improvement in students' test scores after much trial and error. More time with this curriculum change however will help further determine its effectiveness.
Plan B Paper. 2014. Master of Science in Education- Chemistry--University of Wisconsin-River Falls. Teacher Education Department. 28 leaves. Includes bibliographical references (leaves21-22).
Keywords: Chemistry--Study and teaching (Secondary); Student centered learning; Audio-visual education; Individualized instruction